Effects of medical alliance health management model under the perspective of health ecology on mental health of patients with chronic heart failure (健康生态学视域下的医联体健康管理对慢性心衰患者心理健康需求的影响) - HAO Tiantian (郝天天); XU Cuirong (徐翠荣); CAI Xue (蔡雪); XU Xiaolu (徐筱璐); TAN Yaru (谈雅茹) (Journal of International Translational Medicine Limited, 2024)
Objective To explore and analyze the effect of medical alliance health management model under the perspective of health ecology on mental health of patients with chronic heart failure. Methods Two communities under the jurisdiction of community health service centers in a grade A hospital in Nanjing were selected as the research communities and patients form two communities were randomly divided into the experimental group (n=115) and control group (n=103). The experimental group received medical alliance health management model under the perspective of health ecology; the control group was given routine health management education on chronic heart failure prevention and treatment. The intervention period was 12 months, and changes in patients' levels of anxiety, depression and social support before and after the intervention were compared. Results At 12 months after intervention, the Generalized Anxiety Disorder-7 (GAD-7) and Patient Health Questionnaire (PHQ-9) scores were decreased in both experimental group and control group, and GAD-7 and PHQ-9 scores were lower in the experimental group than those in the control group(ITT vs. PP: -1. 07 vs. -1. 07; -0. 45 vs. -0. 49, P＜0. 05). The Social Support Rating Scale(SSRS) score was increased in both experimental group and control group, and SSRS score was higher in the experimental group than that in the control group(ITT vs. PP: 9. 30 vs. 9. 17, P＜0. 05). The generalized linear mixed model showed that the interaction effect of anxiety and social support scores were significant in time and group (P＜0. 05). Conclusion The medical alliance health management model helps to improve the mental health needs and social support of patients with chronic heart failure. (目的 探讨和分析健康生态学视域下的医联体健康管理对慢性心力衰竭患者心理健康需求的影响。方法 选取江苏省南京市某三级甲等医院技术辐射的两个社区卫生服务中心管辖社区作为研究社区, 随机分为试验组(n=115)和对照组(n=103)。试验组采用健康生态学视域下医联体介导的健康管理; 对照组采用慢性心力衰竭健康管理教育。干预周期为12个月, 比较干预前后患者心理健康需求中焦虑抑郁和社会支持水平的变化。结果 干预12个月后, 两组患者广泛性焦虑量表(GAD-7)评分和患者健康问卷抑郁量表(PHQ-9)评分均有所降低, 且试验组与对照组得分差异有统计学意义(ITT vs. PP: -1. 07 vs. -1. 07; -0. 45 vs. -0. 49, P＜0. 05); 社会支持评定量表(SSRS)得分有所提高, 试验组与对照组得分差异有统计学意义((ITT vs. PP: 9. 30 vs. 9. 17, P＜0. 05)。广义线性混合模型结果显示, 两组焦虑抑郁、社会支持得分差异在时间和分组的交互效应均有统计学意义(P＜0. 05)。结论 健康生态学视域下的医联体健康管理有助于改善慢性心力衰竭患者心理健康, 提高社会支持水平。)